GhHB14_D10 and GhREV_D5, two HD-ZIP III transcription factors, play a regulatory role in cotton fiber secondary cell wall biosynthesis - Li, Shuaijie; Yu, Mengli; Qanmber, Ghulam; Feng, Mengru; Hussain, Ghulam; Wang, Yichen; Yang, Zuoren; Zhang, Jie (Plant cell reports, 2024)
Key message GhHB14_D10 and GhREV_D5 regulated secondary cell wall formation and played an important role in fiber development. Cotton serves as an important source of natural fiber, and the biosynthesis of the secondary cell wall plays a pivotal role in determining cotton fiber quality. Nevertheless, the intricacies of this mechanism in cotton fiber remain insufficiently elucidated. This study investigates the functional roles of GhHB14_D10 and GhREV_D5 , two HD-ZIP III transcription factors, in secondary cell wall biosynthesis in cotton fibers. Both GhHB14_D10 and GhREV_D5 were found to be localized in the nucleus with transcriptional activation activity. Ectopic overexpression of GhHB14_D10 and GhREV_D5 in Arabidopsis resulted in changed xylem differentiation, secondary cell wall deposition, and expression of genes related to the secondary cell wall. Silencing of GhHB14_D10 and GhREV_D5 in cotton led to enhanced fiber length, reduced cell wall thickness, cellulose contents and expression of secondary cell wall-related genes. Moreover, GhHB14_D10’s direct interaction with GhREV_D5, and transcriptional regulation of cellulose biosynthesis genes GhCesA4-4 and GhCesA7-2 revealed their collaborative roles in secondary cell wall during cotton fiber development. Overall, these results shed light on the roles of GhHB14_D10 and GhREV_D5 in secondary cell wall biosynthesis, offering a strategy for the genetic improvement of cotton fiber quality.